A Learner's Dictionary of English Idioms - Isabel McCaig, Martin H Manser
Idioms are a very important part of the English language: ou may be told that if you want to go far you should pull your socks up and use your grey matter. An idiom is a phrase which you cannot understand by putting together the meanings of the words in it. For example, pull your socks up has nothing to do with shocks or pulling them up, but means "improve your behavior". This dictionary is for intermediate learners of English who want a clear explanation of the common idioms that are used in contemporary English.